Discretion of the Future: Conceptualizing Everyday Acts of Collective Creativity at the Street‐Level. (3rd June 2021) - Visser, E. Lianne; Kruyen, Peter M.
Abstract: Although scholars and practitioners promote creative uses of discretion in the delivery of public services, there is limited empirical research that explains through which activities street‐level practitioners develop creative solutions. Based on over 300 hours of ethnographic observations of child and family practitioners, we demonstrate the pattern of collective and deliberate experimenting that encompasses creative discretion. The development of this subtype of discretion helps to better analyze and perform it, while simultaneously nuancing the potential positive outcomes of creative uses of discretion for public service provision. Additionally, we explain the collective nature of creative discretion, which has important implications for both research and practice of creativity at the street‐level. Finally, we show that street‐level practitioners become architects of the political and organizational system in which they work by changing the rules and provision, the organization of work, and the development of policy through their performance of creative discretion .